Effect of brimonidine tartrate on basophil activation in glaucoma patients - Rosenfeld, Eldar (Int J Ophthalmol, 2020)
AIM: To evaluate the mechanism of which brimonidine tartrate 0.15% causes clinical hypersensitivity. METHODS: A prospective case-control study comparing 8 glaucoma patients with clinical hypersensitivity to brimonidine to a control group consisting 13 healthy volunteers. Blood samples were stimulated with brimonidine 0.15%, timolol 0.5% or brimonidine tartrate/timolol maleate 0.2%/0.5%. Premixed antibodies (CD63/FITC and aIgE/PE) were added for direct staining and whole-blood samples were lysed, ﬁxed and analyzed by a flow cytometer. The basophil population was defined by high IgE cell expression. Degranulation was identified by the expression of the activation molecule CD63. RESULTS: Basophil activation was not significant when comparing percent of activated basophils of patients and healthy controls after exposure to brimonidine (2.58%, 2.45%, respectively, P=0.72). There was a significant suppression of basophil activation when a combination of brimonidine-timolol (0.87%) was compared to timolol (2.27%; P=0.012) and to brimonidine alone (2.58%; P=0.017). CONCLUSION: The results of our study do not support the hypothesis that brimonidine induces an immediate allergic reaction. Basophil activation was suppressed by the presence of β-blockers in patients hypersensitive to brimonidine and in healthy individuals. This finding indicates that timolol suppress brimonidine drug reaction by a different mechanism.